Optimization of Digital Media Utilization for Anti-Bullying Campaigns Among Generation Z - Triana Rejekiningsih; Dewi Ika Sari; Yudi Ariana; Sri Sumaryati; Taufiq Subhanul Qodr (JTP - Jurnal Teknologi Pendidikan, 2024)
Digital learning media based on applications are rarely found in anti-bullying education, yet the impact of using such learning tools cannot be underestimated. Therefore, this study aims to develop a digital learning media product based on an application to promote anti-bullying among Generation Z in junior high schools. This research adopts a Research and Development (R&D) approach using the ADDIE model, focusing on the process of producing application-based digital learning media suitable for educational purposes. The research subjects consist of media experts, content experts, and the director of the Children's Care Foundation (KAKAK) in Surakarta. Data collection techniques involved media validation questionnaires, which were then analyzed using percentages and described to provide an overview of the suitability level of this media. The research results show that the average validation results were 88%, while the average results from content were 87%. After validation, this digital media fall into the 'Very Good' qualification. Therefore, based on assessments from media experts, content experts, and the director of the KAKAK Foundation, it is concluded that this application-based digital learning media product is categorized as 'feasible' for use as an alternative learning medium in promoting anti-bullying in junior high schools. The existence of this media is evidently an innovative learning tool that enriches the process of anti-bullying education.